Mangalore, Karnataka Fisheries Coast - Manjula Mallya M.; Dr V. Basil Hans (International Journal of Marine Life, 2025)
Mangalore, a major port city on India's southwest coast, is known as the Fisheries Coast of Karnataka due to its thriving marine business and historic fishing legacy. Mangalore's history, economy, and culture are tied to the fishing industry, making it a regional hub for fish landing, processing, and export. The city's Arabian Sea shoreline supports a large fisherfolk community and vital infrastructure such the Mangalore Fishing Harbour, ice plants, cold storages, and fish processing units Sustainable fishing practices, the impacts of climate change, ongoing modernization, and various government initiatives aimed at conserving marine biodiversity and uplifting coastal communities are all key areas of focus in today’s fisheries sector. In this context, Mangalore stands out as a vital center for fisheries in Karnataka, thanks to its strategic coastal location, rich marine resources, and deep-rooted maritime heritage. The region not only contributes significantly to the state’s seafood production but also plays an important role in the livelihoods of local fishing communities, making it a cornerstone of Karnataka’s blue economy.
Keywords: Fisheries; Fishing Industry; Karnataka Coast; Mangalore; Marine Economy; sustainable fishing